Racionalidad de los esquemas de superovulación y sincronización en la transferencia de embriones en bovinos : ¿terapéutica basada en la evidencia o ausencia de ética? (2008)
ABSTRACT: Since the beginning of the use of bovine embryo transfer (ET) in Colombia, hormonal protocols for superovulation (SOV) of donors and for synchronization of recipients (RS) have been used in accordance with protocols reported elsewhere. Several variations of ET protocols have been reported most of they not based in controlled clinical studies but in the supposed pharmacological mechanisms of action of the used hormones, neither with pharmacokinetic studies nor considering the potential collateral effects on cow's fertility. Such collateral effects could be directly or indirectly related with the uncontrolled use of exogenous hormones, or with the time-related additional open days of donor and recipients, without considering the bioethics for animal experimentation. The huge proliferation of protocols for SOV and RS aims for improving both grade I and II (transferable or freezable embryos) embryo yield per transfer, and pregnancy rates for transferred embryos, without having achieved significant improvements during the last 20 years all around the world. In the present review we critic the use of exogenous hormones in bovine ET with emphasis in the rationality of indiscriminating use of exogenous hormones and embryo yield. Finally, we suggest several arguments on the bioethics of the protocols for SOV and RS in bovine ET.